Malaysian Historical Journals (1847-1966):a Bibliometric Study - Tiew, W.S. (Masters of Library of Inf. Sci. Program Uni. of Malaya, 2003)
This article attempts to identify and compile a list of the earliest Malaysian historical journals. The study found that the earliest historical journal is Journal of the Indian Archipelago and Eastern Asia published in 1847 by James Richardson Logan, a well-known lawyer and journalist from the Straits Settlement, British Malaya. Between 1847 till 1966, ten Malaysian historical journals were published by various history-related institutions, associations and individuals. Some of these publications are still active, while others have ceased issuing their journals.